Inovasi Teknologi: Product Display Stand 360 Derajat yang Terkendali dengan Presisi Menggunakan Motor Stepper - Arianto, Eko; Siswoyo, Agus; Hatta, Hendrikus Yori (Politeknik Aceh, 2023)
This article presents the innovation of a 360-degree Product Display Stand designed for showcasing products of varying weights, with a focus on developing the transmission system and stepper motor control. The innovation, a collaborative effort with CV. Songo Industries, resulted in a product capable of displaying a 40 Kg electric wheelchair with high precision. Testing was conducted on various stepper motor configurations using the TB6600 driver, demonstrating that increasing pulse/rev improved the smoothness and strength of the rotational movement, although it slowed down the rotation speed. The stand successfully withstood loads up to 50 Kg and likely can handle even heavier loads. With a reinforced pulley mechanism, the Product Display Stand achieved a total torque of up to 280Kg, surpassing the motor's maximum torque of 20Kg. This study provides a foundation for the development of similar products on a larger scale, such as motorcycles or cars, with appropriate adjustments in mechanical design and transmission. The article invites further collaboration with CV. Songo Industries for advanced custom product development.